Improvement of Physical Education and Sport Efficiency in the Continuous Education System - Shomirzayeva, Nasiba (Maktabgacha taʼlim jurnali, 2022)
This article discusses the formation of a recreational lifestyle with the help of folk games in continuous production. Since, the use of folk games in the lessons develop education.